Use of antimicrobials and antimicrobial resistance in Nepal: a nationwide survey - Komal Raj Rijal; Megha Raj Banjara; Binod Dhungel; Samarpan Kafle; Kedar Gautam; Bindu Ghimire; Prabina Ghimire; Samriddh Dhungel; Nabaraj Adhikari; Upendra Thapa Shrestha; Dev Ram Sunuwar; Bipin Adhikari; et al. (Scientific Reports, 2021)
Abstract Nepal suffers from high burden of antimicrobial resistance (AMR) due to inappropriate use of antibiotics. The main objective of this study was to explore knowledge, attitude and practices of antibiotics uses among patients, healthcare workers, laboratories, drug sellers and farmers in eight districts of Nepal. A cross-sectional survey was conducted between April and July 2017. A total of 516 individuals participated in a face-to-face interview that included clinicians, private drug dispensers, patients, laboratories, public health centers/hospitals and, livestock and poultry farmers. Out of 516 respondents, 62.8% (324/516) were patients, 16.9% (87/516) were clinicians, 6.4% (33/516) were private drug dispensers. A significant proportion of patients (42.9%; 139/324) thought that fever could be treated with antibiotics. Majority (79%; 256/324) of the patients purchased antibiotics over the counter. The knowledge of antibiotics used among patients increased proportionately with the level of education: literate only [AOR = 1.4 (95% Cl = 0.6–4.4)], versus secondary education (8–10 grade) [AOR = 1.8 (95% Cl = 1.0–3.4)]. Adult patients were more aware of antibiotic resistance. Use of antibiotics over the counter was found high in this study. Knowledge, attitude and practice related to antibiotic among respondents showed significant gaps and need an urgent effort to mitigate such practice.